Elaboración de plan de marketing digital para "Perfumería Caricia": creación de identidad de marca, e-commerce y comunicación en redes sociales. - Wong Aparicio, Arianna (2021)
In recent decades, there has been an acceleration in digital communication, from the use of platforms to the way users interact with each other. It is a constantly changing environment, but it is here to stay. Although initially social networks were created for natural persons, the way has been paved for brands to used them to interact with their audiences, giving them a closer relationship with their consumers. Currently, the presence in social networks is almost an obligation for brands, something that was strengthened by the COVID-19 situation where several businesses were forced to digitalize in order to stay afloat. Bearing this in mind, this academic work seeks to analyze and create a digital marketing strategy for the business "Perfumería Caricia" with the aim to adapt it to a digital environment. To do this, a graphic identity of the brand and an e-commerce platform will be developed, alongside with the creation and management of the company's Facebook and Instagram social networks. Through analysis and content creation, it will be possible to communicate and promote the “Perfumería Caricia” business in a digital environment, increasing its sales and customers.